Effect of Cotton Dust Morphology on Photovoltaic Module Performance - Ali, Basit; Khan, M. Faisal; Ishaque, Kashif (2024 International Conference on Emerging Trends in Smart Technologies (ICETST), 2024)
The use of renewable energy is increasing due to the high cost of conventional fuels and climate issues. Textile industries, specifically in Asian region, are shifting towards large PV plants in order to acquire cheap and clean energy. However, cotton dust presence in the textile mill environment causes performance issues for PV modules. This study examines the cotton dust particle effect on PV module by employing an experimental methodology. An indoor experimental setup is utilized to test the PV modules in two schemes, that are clean and dusty. The experiment is conducted for eight days with an hourly interval. It is observed that PV power output reduces significantly up to 15% in eight days as compared to clean PV module. The deposited cotton dust particles are also physically examined through compound microscope in order to determine its physical nature. It is being observed that cotton particles are composed of long, smooth fibers with irregular shapes. The particles are highly influenced by humidity, and their own high content of cellulose makes them vulnerable to stick on the PV surface and forming clumps and aggleromates that develop the hotspots on the PV surface. Along with that, as time progresses the cotton dust opaqueness also increases, ultimately reducing the transmittance and decreasing PV module performance. This study helps to devise a unique cleaning patterns and methods for textile units to enhance performance output.